Immunoreactivity of synthetic peptides derived from proteins of Cryptococcus gattii - Santos de Serpa Brandao, Rafael Melo; Soares Martins, Liline Maria; Andrade, Helida Monteiro de; Faria, Angelica Rosa; Soares Leal, Maria Jose; Silva, Adalberto Socorro da; Wanke, Bodo; Lazera, Marcia dos Santos; Vainstein, Marilene Henning; Mendes, Rinaldo Poncio [UNESP]; Moris, Daniela Vanessa [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; et al. (Future Medicine Ltd, 2014)
Aim: To determine the immunoreactivity of synthetic Cryptococcus-derived peptides. Materials & methods: A total of 63 B-cell epitopes from previously identified Cryptococcus gattii immunoreactive proteins were synthesized and evaluated as antigens in ELISAs. The peptides were first evaluated for their ability to react against sera from immunocompetent subjects carrying cryptococcal meningitis. Peptides that yielded high sensitivity and specificity in the first test were then retested with sera from individuals with other fungal pathologies for cross-reactivity determination. Results: Six of 63 synthetic peptides were recognized by antibodies in immunoassays, with a specificity of 100%, sensitivity of 78% and low cross-reactivity. Conclusion: We successfully determined the immunoreactivity of selected synthetic peptides of C. gattii derived proteins.
Keywords: antigens; cryptococcosis; diagnosis; ELISA; synthetic peptides